2022
DOI: 10.1186/s12889-022-13379-3
|View full text |Cite
|
Sign up to set email alerts
|

Shifting educational gradients in body mass index trajectories of Indonesians: an age period cohort analysis

Abstract: Background Globally, the number of obese adults has increased rapidly in many developing countries. The links between increased educational attainment and lower risks of overweight/obesity have been studied in a number of high-income contexts. However, educational attainment can have a different association with obesity at different levels of economic development and different stages of the nutritional transition, and these associations may vary by period and cohort. This study aims to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This approach additionally assumes that all selected IVs must be conditionally independent of the outcome, given all exposures and confounders ( Sanderson et al, 2019 ). Studies have found the associations between EA and body mass index (BMI) ( Liwin, 2022 ; Zhang et al, 2022 ; Zhao et al, 2022 ), alcoholic drinks per week ( Liu et al, 2019 ; Treur et al, 2021 ; Zhou et al, 2021 ). In addition, BMI of parents is well-established influencing factor for offspring birth weight according to both clinical observational and genetic association studies ( Vogelezang et al, 2020 ; Chen S. et al, 2021 ; Thompson et al, 2021 ; Aydogan Mathyk et al, 2022 ; Gootjes et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This approach additionally assumes that all selected IVs must be conditionally independent of the outcome, given all exposures and confounders ( Sanderson et al, 2019 ). Studies have found the associations between EA and body mass index (BMI) ( Liwin, 2022 ; Zhang et al, 2022 ; Zhao et al, 2022 ), alcoholic drinks per week ( Liu et al, 2019 ; Treur et al, 2021 ; Zhou et al, 2021 ). In addition, BMI of parents is well-established influencing factor for offspring birth weight according to both clinical observational and genetic association studies ( Vogelezang et al, 2020 ; Chen S. et al, 2021 ; Thompson et al, 2021 ; Aydogan Mathyk et al, 2022 ; Gootjes et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a previous study in Indonesia suggested that higher education, and white scholar workers were associated with higher BMI [18]. The reasons for this might be in Indonesia, higher education is related to better socioeconomic status [17]; however, socioeconomic level was not significantly influenced by self-reported health status [48], and people with higher socioeconomic status are more likely to experience health issues like obesity and hypertension [49, 50]. Furthermore, greater BMI in the middle age category has been linked to an increase in stroke and myocardial infraction [51], the highest association with incident heart failure among CVD subtypes [52], and may increase the risk of heart disease [41], which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, a previous study using IFLS data found that between 1993 and 2014, the prevalence of overweight people doubled from 17.1% to 33.0%, and the younger generations have higher BMIs than the older generations [17]. The mean BMI also increased from 21.4 kg/m 2 in 1993 to 23.85 kg/m 2 in 2014 [17, 18]. Furthermore, based on the BMI Asian populations classification, in Indonesia, overweight and obesity were more common in women than men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 to 2019-21, the largest absolute increase in prevalence occurred for unhealthy weight (overweight or obesity: 3•4 percentage points, 95% CI: 3•0, 3•8; obesity: 1•2 percentage points, 95% CI 1•0, 1•3) followed by diabetes (0•3 percentage points, 95% CI 0•2, 0•5) (Table2). While the absolute changes appear small, these increasing trends corresponded to pronounced relative changes when compared to the baseline NFHS-4 values: overweight or obesity increased by 17% (95% CI 14•7, 19•3) from a baseline prevalence of 20% (95% CI 19•7; 20•3), obesity by 28•4% (95% CI 23•7, 33•2) from a baseline prevalence of 4•1% (95% CI 4•0, 4•2), and diabetes by 9•5% (95% CI 4•4, 14•7) from a baseline prevalence of 3•3% (95% CI 3•2, 3•4).…”
mentioning
confidence: 99%